2016
DOI: 10.15567/mljekarstvo.2016.0303
|View full text |Cite
|
Sign up to set email alerts
|

Protein profiles and total antioxidant capacity of water soluble and insoluble protein fractions of white cow cheese at different stage of ripening

Abstract: This research is focused on proteolysis and total antioxidant capacity of proteins of white brined cheese prepared from overheated (90 °C, 10 minutes) cow milk. White brined cow cheese of overheated milk went through specific proteolytic changes during ripening that were result of high level of whey proteins incorporated into the gel matrix. Specificity was reflected through the relatively low level of soluble nitrogen fractions, the intensive and continual decrease of α s -caseins up to 15.42 % of initial con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 20 publications
0
16
0
3
Order By: Relevance
“…A study was performed to assess the antioxidant properties of peptides cheese ripening for six months, HPLC characterization revealed that antioxidant properties of cheese were strongly correlated with water-soluble peptides, DPPH free radicals scavenging activity of matured cheese was more than 95% [ 34 ]. Antioxidant characteristics of white brined cheese were investigated, antioxidant activity of water-soluble and fat-soluble fractions increased during the ripening [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study was performed to assess the antioxidant properties of peptides cheese ripening for six months, HPLC characterization revealed that antioxidant properties of cheese were strongly correlated with water-soluble peptides, DPPH free radicals scavenging activity of matured cheese was more than 95% [ 34 ]. Antioxidant characteristics of white brined cheese were investigated, antioxidant activity of water-soluble and fat-soluble fractions increased during the ripening [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…3). Namely, considering antioxidant properties of caseins and whey proteins that are incorporated into the protein matrix of cheese, Barać et al (2016) assumed that the water-insoluble fraction possesses an antioxidant potential as well. According to the results of these studies both protein fractions had a great antioxidant capacity, which was in range of capacities of plant protein products (Žilić et al, 2012) that are characterized as functional.…”
Section: Antioxidant Peptides Of White Cheese In Brinementioning
confidence: 99%
“…Antioksidan peptitler gıdaların oksidatif bozulmalarını önlemek suretiyle raf ömürlerini uzatmaları açısından da önemlidir (De Gobba ve ark., 2014). Bu peptitler çoğunlukla starter ve starter olmayan laktik asit bakterilerinin etkisiyle kazeinlerden açığa çıkmaktadır (Barac, 2016). Yapılan çalışmalar, laktik asit bakterilerinin proteolitik enzimlerinin etkisiyle özellikle αs-kazein fraksiyonundan elde edilen hidrolizatların antioksidan aktiviteye sahip olduğunu göstermiştir (Korhonen ve Pihlanto-Leppälä, 2006;Haque ve ark., 2009;Beermann ve Hartung, 2013).…”
Section: Antitrombotik Etkiunclassified
“…Peynir üretimi sırasında oluşan peptitler son ürünün tat, aroma ve tekstürüne katkı sağlarken aynı zamanda bu bileşenler peynirde antihipertansif, opioid, antimikrobiyal ve antioksidan etki de oluşturabilmektedir (Timon ve ark., 2014;Sánchez-Rivera ve ark., 2014;Erkaya ve Şengul, 2015). Son yıllarda fermente süt ürünleri gibi peynirler de biyoaktif peptitler için önemli bir kaynak olarak kabul edilmektedir (Barac, 2016). Çizelge 2'de bazı peynirlerde tanımlanan biyoaktif peptitler ve aktiviteleri verilmiştir.…”
Section: Peynirde Biyoaktif Peptitlerunclassified